Hypopharyngeal‐Esophageal Impedance‐pH Monitoring Profiles of Laryngopharyngeal Reflux Patients. (21st May 2020) - Lechien, Jerome R.; Bobin, Francois; Dapri, Giovanni; Eisendrath, Pierre; Salem, Charelle; Mouawad, Francois; Horoi, Mihaela; Thill, Marie‐Paule; Dequanter, Didier; Rodriguez, Alexandra; Muls, Vinciane; Saussez, Sven
Abstract : Objectives/Hypothesis: To investigate the profile of patients with laryngopharyngeal reflux (LPR) at hypopharyngeal–esophageal multichannel intraluminal impedance‐pH (HEMII‐pH) monitoring and the relationship between hypopharyngeal‐proximal reflux episodes (HREs) and saliva pepsin concentration. Study Design: Prospective non‐controlled. Methods: Patients were recruited from three European hospitals from January 2018 to October 2019. Patients benefited from HEMII‐pH monitoring and saliva collections to measure saliva pepsin concentration in the same time. Saliva pepsin concentration was measured in the morning (fasting), after lunch, and after dinner. The LPR profile of patients was studied through a breakdown of the HEMII‐pH findings over the 24 hours of testing. The relationship between the concentrations of saliva pepsin and 24‐hour HREs was studied through linear multiple regression. Results: One hundred twenty‐six patients completed the study. The HEMII‐pH analyses revealed that 73.99% of HREs occurred outside 1‐hour postmeal times, whereas 20.49% and 5.52% of HREs occurred during the 1‐hour postmeal and nighttime, respectively. Seventy‐four patients (58.73%) did not have nighttime HREs. Patients with both daytime and nighttime HREs had more severe HEMII‐pH parameters and reflux symptom score compared with patients with only daytime HREs. There were no significant associations between HREs and saliva pepsin concentration. Conclusions: Unlike gastroesophageal reflux disease, HREs occur less frequently after meals and nighttime. The analysis of the HEMII‐pH profile of the LPR patients has to be considered to develop future personalized therapeutic strategies. Level of Evidence: 4 Laryngoscope, 131:268–276, 2021